Preliminary Correlations for Remotely Piloted Aircraft Systems Sizing - Álvaro Gómez-Rodríguez; Alejandro Sanchez-Carmona; Luis García-Hernández; Cristina Cuerno-Rejado (Aerospace, 2018)
The field of Remotely Piloted Aircraft Systems (RPAS) is currently undergoing a noteworthy expansion. The diverse types of missions that these aircraft can accomplish, both in military and civil environments, have motivated an increase of interest in their study and applications. The methods chosen to develop this study are based on the statistical analysis of a database including numerous models of RPAS and the estimation of different correlations in order to develop a design method for rapid sizing of H-tail RPAS. Organizing the information of the database according to relevant characteristics, information relative to the state-of-the-art design tendencies can be extracted, which can serve to take decisions relative to the aerodynamic configuration or the power plant in the first phases of the design project. Furthermore, employing statistical correlations estimated from the database, a design method for rapid-sizing of H-tail RPAS has been conducted, which will be focused on the sizing of the wing and tail surfaces. The resulting method has been tested by applying it to an example case so as to validate the proposed procedure.